THE ROLE OF TNF-Α IN THE DEVELOPMENT OF DIABETIC NEPHROPATHY IN THE SOUTHERN ARAL SEA REGION - Najmutdinova D. K.; Sultanov Sh. B. (The Conference Hub, 2025)
Diabetic nephropathy (DN) remains one of the most serious microvascular complications of type 2 diabetes mellitus (T2DM), leading to chronic kidney disease (CKD) and eventually end-stage renal failure. Among the numerous pathogenic mechanisms involved, chronic low-grade inflammation plays a pivotal role, with tumor necrosis factor-alpha (TNF-α) recognized as a key pro-inflammatory cytokine contributing to the progression of renal injury. The Southern Aral Sea region, affected by long-term ecological degradation, presents unique environmental challenges that may influence the pathophysiology of diabetes-related complications.